Increasing Student Learning Interest With the Jigsaw Type Cooperative Model in Physical Education Learning Sports and Health - Cahyono, Nugroho Dwi; Dinata, Vega Candra; Arifin, Zainal (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
The method used in this study was classroom action research and was carried out to assess the application of the jigsaw cooperative learning model to PJOK subjects with the topic of healthy lifestyle patterns during the month of Ramadan. This study used class 5 B subjects at UPT SDN 144 Gresik for the 2022/2023 academic year, with a total of 24 students. Observation sheets, questionnaires, and tests are the instruments used in this study. The data analysis used is a qualitative quantitative technique. The result is an increase starting from the pre-cycle, cycle I, and cycle II. Students' interest in pre-cycle shows a percentage of 60.6%, Cycle 1 shows a percentage of 71.8%, and Cycle II shows a percentage of 81.9%. While the learning outcomes of the initial ability of the class average of 68.75 the percentage of completeness is 42%, the first cycle of the class average is 76.66 the percentage of completeness is 63%, the second cycle the average class is 90.83 the percentage of completeness is 87%. So, the cooperative learning of the jigsaw model in general can increase learning interest and student learning outcomes in PJOK subjects, especially during learning in the month of Ramadan.